Electrochemical sensors for the detection of immune checkpoint related proteins and their role in cancer companion diagnostics - Louise Barnaby; Andrew G. Watts; Pedro Estrela (Biosensors and Bioelectronics: X)
Cancer companion diagnostics are incredibly important in helping to determine whether a patient will benefit from immune checkpoint inhibitor (ICI) treatment. Determining the chances of treatment success helps to inform clinicians to make the best treatment decisions for a particular patient. Many immune checkpoint related proteins show potential as biomarkers for ICI success, such as the checkpoint proteins themselves, cytokines, interleukins and other immune response related proteins. The most investigated checkpoint inhibitor protein is Programmed Death Ligand 1 (PD-L1), which is used as a biomarker in clinical diagnostic tests but, with some limitations. In the near future, tests for many different biomarkers will start becoming commercially available along with tests for multiple biomarkers simultaneously, giving an even better prediction of potential ICI success. Electrochemical sensors are a high sensitivity point of care diagnostic technique that can have the potential to achieve detection of multiple biomarkers at once. The main problem facing this field is improving their sensitivity to be able to detect the incredibly low concentrations of biomarkers found in liquid biopsy samples. Many methods such as enhancing an electrode surface with high conductivity materials or increasing the measured electrochemical signal via signal amplifying molecules have been investigated with promising results. This review investigates the potential biomarkers relevant to predicting ICI success, as well as the current electrochemical sensors that have been developed to determine the expression levels of these proteins.